Effects of Carbon Dioxide on Quality of Babycorn (Zea mays Linn.) CV. Supersweet - Sasitorn Ittanuvakin (Agriculture and Natural Resources, 1992)
Babycorn cv. Supersweet stored in glassjars containing 5, 10, 15 and 20% CO2 90% relative humidity at 25 degree + 2 degree C. It was found that higher CO2 concentration reduced weight-loss, browning, fungal appearance and delayed the decreasing in soluble solids contents. Consequently, babycorn under high CO2 could be stored in good condition for a longer period of time. When CO2 concentration was increased to 10, 20, 30 and 40% in another experiment, lower fungal appearance was found in higher CO2 atmosphere. However, the CO2 concentrations between 20-40% were harmful to babycorn, causing more browning.